2011
DOI: 10.1007/s11845-011-0738-9
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management of chronic anticoagulation therapy in urological patients: a cross-sectional survey of practice

Abstract: Our study demonstrates variations in perioperative management practices for patients on chronic anticoagulation therapy undergoing urological procedures. Urologists should familiarise themselves with standardised guidelines if this patient subgroup are to receive optimal perioperative management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
7
0
3
Order By: Relevance
“…The perioperative management of these medications remains a challenge for most dermatologists. In dermatology but also in other disciplines, health care research has shown large heterogeneity in the perioperative management of anticoagulation . In a cross‐sectional study in Germany, 40% of the dermatologists working in dermatosurgery in hospitals would recommend stopping low‐dose (<100 mg) aspirin prior to large excision, whereas 54% would recommend to continue the treatment (no answer 6.2%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perioperative management of these medications remains a challenge for most dermatologists. In dermatology but also in other disciplines, health care research has shown large heterogeneity in the perioperative management of anticoagulation . In a cross‐sectional study in Germany, 40% of the dermatologists working in dermatosurgery in hospitals would recommend stopping low‐dose (<100 mg) aspirin prior to large excision, whereas 54% would recommend to continue the treatment (no answer 6.2%).…”
Section: Introductionmentioning
confidence: 99%
“…In dermatology but also in other disciplines, health care research has shown large heterogeneity in the perioperative management of anticoagulation. [2][3][4] In a cross-sectional study in Germany, 40% of the dermatologists working in dermatosurgery in hospitals would recommend stopping low-dose (<100 mg) aspirin prior to large excision, whereas 54% would recommend to continue the treatment (no answer 6.2%). With respect to VKA, 63% of hospital-based dermatologists would recommend stopping or bridging with heparin, whereas 33.8% would recommend to continue with the treatment (no answer: 3.1%).…”
Section: Introductionmentioning
confidence: 99%
“…Dabei zeigen sich in der Dermatologie wie auch in anderen Fachrichtungen große Unterschiede im Umgang mit antithrombotischen Mitteln bei chirurgischen Eingriffen . Im Jahre 2012 wurde dieser im Rahmen einer Befragung in dermatologischen Praxen und Kliniken in Deutschland untersucht .…”
Section: Einführungunclassified
“…In dermatology, as in other specialties, there are large differences with respect to perioperative management of antithrombotic agents . In 2012, we investigated this issue in a survey of office‐ and hospital‐based dermatologsts in Germany .…”
Section: Introductionmentioning
confidence: 99%